Troxerutin protect sperm, seminiferous epithelium and pituitary-gonadal axis from torsion-detorsion injury: An experimental study - Abdolreza Kheirollahi; Abolfazl Abbaszadeh; Khatereh Anbari; Behrouz Rostami; Amirhossein Ahangari; Afshin Hasanvand; Mohammadreza Gholami (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Troxerutin is a flavonoid antioxidant that protect different organ against damage caused by ischemia-reperfusion. Objective: The aim of this study was to evaluate the effect of troxerutin in reducing the damages caused by ischemia-reperfusion in rat's testis. Materials and Methods: 40 Male Wistar rats (2 month old) were divide to four groups (n=10). Group1 (sham), Group 2 (control, ischemia-reperfusion (I/R) without treatment), Group 3 (I/R+150 mg/kg of troxerutin), and group 4 (I/R+20 mg/kg of vitamin C). Treatment of group 3 and group 4 during torsion (twists 720 counter clock at 90 min) followed by 50 days detorsion. After 50 days, blood samples were collected and rats in all study groups were killed and their testes were removed, and fixed with Bouin’s solution. Testis was stained with hematoxylin and eosin dye and the level of testosterone, luteinizing hormone (LH) and follicle-stimulating hormone (FSH) were measured with ELISEA methods. TUNEL was employed to detect apoptosis. Epididymis caudal part was removed and total sperm count was determined. Johnson techniques were used for assessment of seminiferous tubules quality. Results: Troxerutin treated group has higher Johnson score’s (p≤0.001), antiapoptotic properties (p≤0.001), sperm count (p=0.065), and higher LH (p≤0.001), FSH (p≤0.001) and testosterone (p=0.002) levels than control group. Vitamin C treated group showed increase level of testosterone but didn’t show significant differences on the number of apoptotic cells, Johnson scores, LH, FSH and sperm count than control group. Conclusion: Troxerutin has protective effects on testicular torsion induced injury and can ameliorate spermatogenesis in the torsion-detorsion models.